Pregnancy outcome in pre-gestational and gestational diabetic women: a prospective observational study - Mahajan, Mamta; Gupta, Amit; Vij, Anju; Sharma, Aanchal Gupta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: India is considered the world capital of diabetes, proper care and management of the same is the demand of society. The present study is carried out to identify the disease burden of GDM/ overt DM among antenatal cases. The main objective was to study the maternal and fetal outcome of diabetes complicating pregnancy. Methods: The present study was conducted at Dr. Rajendra Prasad Government Medical College at Tanda, District KangraHP from October 2015 to September 2016. All antenatal cases were screened for diabetes by OGTT 75 gm, 2-hour blood glucose level as per DIPSI guidelines and labelled as GDM/ overt DM. Those who fulfilled selection criteria were enrolled in the study. A total of 6452 cases who attended antenatal clinic during the study duration and were screened were selected for the study. 116 cases were found to have GDM / overt DM. Seventy-nine had GDM with OGTT>140 mg/dl (DIPSI guidelines) and 37 had overt DM with 2 hours PP >200 mg/dl (WHO criteria). Total 100 cases comprised of study group were followed till delivery to study maternal and fetal outcome. Results: The prevalence of diabetes in pregnancy was found to be low 1.79%. GDM was found to be more prevalent than overt diabetes in pregnant women (66% versus 34%). Among the antenatal maternal complications observed missed abortion (11.8% versus 1.55; p=0.026), polyhydraminos (26.4% versus 10.6%; p=0.04) and preterm labour (17.6% versus 4.5%; p=0.003) were significantly more common in overt diabetics than GDM cases. IUFD (8.8% versus 0; p=0.014) was also significantly more common in overt diabetics than GDM case. RDS was found significantly higher in neonates of overt diabetics as compared to GDM mothers (14.7 % versus 1.5%; p=0.009). Conclusions: Early detection and good glycemia control by MNT and insulin, regular antenatal check-ups, patient counselling and compliance, intrapartum fetal monitoring and early neonatal care are keys to improved outcome.